The labor market in Panama: An analysis of the employment impact of the labor code - Dean Spinanger (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1984)
This study represents an attempt to determine to what degree well-meant labor market policies negatively influence employment and hence unemployment levels. To do this a survey - referred to hereafter as the Labor Code Survey (LCS) - of firms in Panama was carried out. This survey is unique not only for Panama - such a broad-based attempt to analyze the impact of labor market regulations has not been carried out anywhere else. The study as it stands, however, is not considered by the author to be complete, as neither the entire depth of the information gathered for the project could be presented here, nor are possible issues from the employees' side explicitly covered in this approach. The author would thus welcome comments on issues which could be analyzed further and criticism of aspects neglected or overly stressed.
Keywords: 330